Effects of combined renin–angiotensin–aldosterone system inhibitor and beta‐blocker treatment on outcomes in heart failure with reduced ejection fraction: insights from BIOSTAT‐CHF and ASIAN‐HF registries. (25th June 2020) - Ouwerkerk, Wouter; Teng, Tiew‐Hwa K.; Tromp, Jasper; Tay, Wan Ting; Cleland, John G.; van Veldhuisen, Dirk J.; Dickstein, Kenneth; Ng, Leong L.; Lang, Chim C.; Anker, Stefan D.; Zannad, Faiez; Hung, Chung‐Lieh; et al.
Abstract: Background: Angiotensin‐converting enzyme inhibitors (ACEi)/angiotensin receptor blockers (ARB) and β‐blockers are guideline‐recommended first‐line therapies in heart failure (HF) with reduced ejection fraction (HFrEF). Previous studies showed that individual drug classes were under‐dosed in many parts of Europe and Asia. In this study, we investigated the association of combined up‐titration of ACEi/ARBs and β‐blockers with all‐cause mortality and its combination with hospitalization for HF. Methods and results: A total of 6787 HFrEF patients (mean age 62.6 ± 13.2 years, 77.7% men, mean left ventricular ejection fraction 27.7 ± 7.2%) were enrolled in the prospective multinational European (BIOSTAT‐CHF; n  = 2100) and Asian (ASIAN‐HF; n  = 4687) studies. Outcomes were analysed according to achieved percentage of guideline‐recommended target doses (GRTD) of combination ACEi/ARB and β‐blocker therapy, adjusted for indication bias. Only 14% ( n  = 981) patients achieved ≥50% GRTD for both ACEi/ARB and β‐blocker. The best outcomes were observed in patients who achieved 100% GRTD of both ACEi/ARB and β‐blocker [hazard ratio (HR) 0.32, 95% confidence interval (CI) 0.26–0.39 vs. none]. Lower dose of combined therapy was associated with better outcomes than 100% GRTD of either monotherapy. Up‐titrating β‐blockers was associated with a consistent and greater reduction in hazards of all‐cause mortality (HR for 100% GRTD: 0.40, 95% CI 0.25–0.63) than corresponding ACEi/ARB up‐titration (HR 0.75, 95% CI 0.53–1.07). Conclusion: This study shows that best outcomes were observed in patients attaining GRTD for both ACEi/ARB and β‐blockers, unfortunately this was rarely achieved. Achieving >50% GRTD of both drug classes was associated with better outcome than target dose of monotherapy. Up‐titrating β‐blockers to target dose was associated with greater mortality reduction than up‐titrating ACEi/ARB.